TRANSFORMASI DIGITAL USAHA DAGANG TRADISIONAL: STUDI KUALITATIF PADA RITEL GROSIR KELUARGA DI BANJARMASIN - Nisrina Ayu Lestari; Mohammad Adhiya Riswandha (Smart Business Journal (SBJ), 2025)
This study aims to analyze digital innovation strategies in family-owned wholesale retail stores as an effort to increase competitiveness and business sustainability amidst competition from modern retailers. The study employed a qualitative approach with primary data obtained through in-depth interviews, direct observation, and document study. The research object was a family-owned wholesale retail store (Store X) in Banjarmasin that has gradually implemented digitalization in its operations. The results show that Store X has adopted digital innovation using a Point of Sale (POS) system, marketplace utilization, online ordering services via WhatsApp, cashless payments, and delivery services. This strategy has proven effective in improving operational efficiency, expanding market reach, and enhancing customer satisfaction. However, the digitalization effort still faces several challenges, particularly internally, such as lack of real-time integrated stock management, limited human resources, and the lack of structured digital strategic planning. This study concludes that digital innovation in family-owned wholesale retail stores serves not only as an operational support tool but also as an adaptive strategy to address changing consumer behavior and business competition. Therefore, it is necessary to strengthen human resource capacity, integrate internal management systems, and implement long-term digital planning so that the digital transformation of MSMEs can run optimally and sustainably